Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: \(\frac{4^6.25^5-2^{12}.25^4}{2^{12}.5^8-10^8.64}=\frac{2^{12}.5^{10}-2^{12}.5^8}{2^{12}.5^8-2^8.5^8.2^6}\)
\(=\frac{2^{12}.\left(5^{10}-5^8\right)}{2^{12}.5^8-2^{14}.5^8}\)
\(=\frac{2^{12}.5^8.\left(5^2-1\right)}{5^8.\left(2^{12}-2^{14}\right)}\)
\(=\frac{2^{12}.5^8.24}{5^8.2^{12}.\left(1-2^2\right)}\)
\(=\frac{24}{-3}\)
\(=-8\)
Học "tuốt" nha^^
a) 169/196
b) 1/144
c) \(\frac{5^4.20^4}{25^5.4^5}=\frac{\left(5.20\right)^4}{\left(25.4\right)^5}=\frac{100^4}{100^5}=\frac{1}{100}\)
d) -2506/3
a)=3^4<3.n<3^10
=>n=4;5;6;7;8;9
b)5^2<5^n-1<5^4
=>n-1=3=>n=4
c)5.5^2n==5^6
=>5^2n+1=5^6
=>n=7/2
25^44*25^6=25^44+6=25^50
6^2:6^1=6^2-1=6^1
2544.256=2544+6=2550
62:61=62-1=61=6